2017
DOI: 10.1515/opag-2017-0061
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod sensitivity of very early maturing Sri Lankan rice for flowering time and plant architecture

Abstract: Unavailability of information on photoperiod sensitivity of traditional rice is a disadvantage in breeding rice for adaptation to changing climatic conditions and for optimum plant architecture. This experiment was conducted to address the above problem through determination of variation in days to flowering (DF) and morphological traits of twenty eight selected very early maturing Sri Lankan traditional rice accessions under three photoperiod conditions: short day (SD), day neutral (DN) and long day (LD). Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…To secure food particularly rice for the growing population, additional pressure on agriculture resources is expected (Yang et al 2018). National rice production can be reduced by adverse climatic and environmental conditions (Padukkage et al 2017). Maintaining soil health and restoring degraded agricultural land are the major strategies that need to be adapted.…”
Section: Introductionmentioning
confidence: 99%
“…To secure food particularly rice for the growing population, additional pressure on agriculture resources is expected (Yang et al 2018). National rice production can be reduced by adverse climatic and environmental conditions (Padukkage et al 2017). Maintaining soil health and restoring degraded agricultural land are the major strategies that need to be adapted.…”
Section: Introductionmentioning
confidence: 99%
“…The heading date (flowering time) is an important trait for the regional and seasonal adaptation of rice and influences grain yield [4]. Thus, photoperiod-sensitive control in rice is essential for the production of rice adaptive to different climatic conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…The primary distinction between landrace and improved rice varieties lies in their photoperiod sensitivity [5]. Rice landraces flower under short-day conditions [5], while improved rice can flower throughout the year, given sufficient time for the preproduction stage. Previous studies on heading dates focused on genotypic photoperiod-sensitive rice cultivars [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that traditional rice cultivars from tropical regions are photoperiod sensitive and require between 160-170 days to mature (Vergara & Chang,1985;Viraktamath, 2013;Nandini, 2020;Khotasena et al, 2022). Most of the studies on photoperiodism of traditional rice in the tropics are from Cambodia (Makara et al, 2001;Tsubo et al, 2009;Uch et al, 2023), Thailand (Cha-um & Kirdmanee, 2007;Boling et al, 2011;Sujariya et al, 2023), and Sri Lanka (Mapalana, 2017;Padukkage et al, 2017;Rathnathunga et al, 2019). The geographical locations of these countries are within 7.9 °N-15.9 °N latitude, thus experiencing different changes in day length throughout the year.…”
Section: Introductionmentioning
confidence: 99%